Macherla: A new mutton type sheep population of southern India - MISHRA, A K; N, RAJA K; VINOO, R; SURENDRA, K; DANGI, P S (The Indian Journal of Animal Sciences, 2021)
Phenotypic characterization and evaluation of Macherla sheep population was done by undertaking survey in Guntur and Prakasham districts of Andhra Pradesh. Macherla animals are medium to large in size, mainly in white coat colour with large brown or black patches in the body, face and legs. The animals with brown patches are known as Macherla brown in breeding area. Convex nasal bridge, leafy ears, black muzzle and black/brown and white coat colour is predominant. Males are horned and females are polled, however some females are noticed with horns in few flocks. The horns are oriented backward, downward and forward. Ears are medium to large in size and leafy/semi-drooping. Tail is very small and thin. The adult body weight ranged from 38 to 69 kg in rams and 25 to 60 kg in ewes. The overall body length, height, chest girth, face length, face width, ear length and tail length were 70.07±0.32, 77.05±0.31, 87.75±0.41, 25.46±0.21, 10.49±0.08, 16.11±0.09 and 9.67±0.15 cm, respectively. The study revealed that the Macherla sheep is phenotypically different from other sheep breeds of the region and famous for mutton production as well as livelihood security of the farmers maintaining this sheep population.